Pattern and Outcome of Acute Appendicitis: Observational Prospective Study from a Teaching Hospital, Addis Ababa, Ethiopia - Gebre Selassie H (Open Access Emergency Medicine, 2021)
Hana Gebre Selassie,1 Henok Tekle Selassie,2 Daniel Ashebir2 1Department of Surgery, St. Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia; 2Department of Surgery, Addis Ababa University, College of Health Sciences, Addis Ababa, EthiopiaCorrespondence: Hana Gebre SelassieDepartment of Surgery, St. Paul’s Hospital Millennium Medical College, Addis Ababa, EthiopiaTel +251913766868Email hanaabebe23@gmail.comBackground: Acute appendicitis is the most common cause of acute abdomen surgery. Despite its commonness and the abundance of literature on the subject, its diagnosis remains challenging. Delay in intervention results in complications of the process leading to increased morbidity and mortality.Methodology: An observational prospective cohort study was conducted, and all patients who had undergone appendectomy for a clinical diagnosis of appendicitis were included in the study. Data were analysed using Statistical Package for Social Sciences (SPSS) version 23.Results: Half of the study participants were in the age range of 18– 25 years with male preponderance (63.9%). The mean duration of symptoms was 51.3 hours. The most common presenting symptom was abdominal pain (98.2%), while right lower quadrant tenderness was the most common sign (93.4%). Abdominal ultrasound was done in 81% of the study population with a sensitivity and specificity of 95.7% and 33.3%, respectively. Three-quarters (74.4%) of the patients had uncomplicated appendicitis, while 1.8% had a grossly normal appendix. None of the appendectomy specimens were sent for pathology. The mean hospital stay was 3.2 days. The morbidity and mortality rate were 3.8% and 0.4%, respectively.Conclusion: Acute appendicitis was the most common emergency surgical procedure in the study period. Abdominal ultrasound was used in the majority of the patients as supplementary imaging for the diagnosis of acute appendicitis. Uncomplicated appendicitis took the major share of the intraoperative finding leading to acceptable morbidity and mortality rates.Keywords: acute appendicitis, simple appendicitis, complicated appendicitis, morbidity, mortality